2003
DOI: 10.18474/0749-8004-38.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Selected Insecticides on the Population Dynamics of Diamondback Moth (Lepidoptera: Plutellidae) and Its Parasitoid, Diadegma insulare (Hymenoptera: Ichneumonidae), in Cabbage

Abstract: The effects of insecticides on the diamondback moth, Plutella xylostella (L)., and its parasitoid, Diadegma insulare (Cresson), were evaluated in the field. Insecticides applied for control of the diamondback moth caused variations in parasitism by D. insulare ranging from 20 to 84%. Permethrin applications were effective at controlling diamondback moth. Applications of spinosad also resulted in low diamondback moth populations; however, percent parasitism was higher than in untreated plots and over 4× higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…Liu et al (2012a) observed one-third as much parasitism on lambda-cyhalothrin treated broccoli as on nontreated plants, but no effect was observed with spinosad. Hill and Foster (2003) observed greater parasitism in plots treated with spinosad than in untreated plots. Therefore, we reduced parasitism for a HTI.…”
Section: Methodsmentioning
confidence: 77%
“…Liu et al (2012a) observed one-third as much parasitism on lambda-cyhalothrin treated broccoli as on nontreated plants, but no effect was observed with spinosad. Hill and Foster (2003) observed greater parasitism in plots treated with spinosad than in untreated plots. Therefore, we reduced parasitism for a HTI.…”
Section: Methodsmentioning
confidence: 77%
“…Hill and Foster (2000) reported spinosad caused 100% mortality of D. insulare 8 h after treatment under laboratory conditions. However, in a follow-up study, parasitism of P. xylostella larvae was not affected by spinosad application under Þeld conditions (Hill and Foster 2003). In general, it appears that hymenopteran parasitoids are more susceptible to spinosad than predatory insects (Williams et al 2003).…”
Section: Discussionmentioning
confidence: 95%
“…Several factors can inßuence the nontarget impact of an insecticide in the Þeld. For example, spinosad was extremely toxic to the hymenopteran parasitoid Diadegma insulare (Cresson) in leaf dip assays (Hill and Foster 2000); however, in Þeld experiments D. insulare parasitism of diamondback moth larvae was not affected by spinosad applications (Hill and Foster 2003). In addition, the aforementioned insecticides may have sublethal effects on natural enemies, such as parasitoid oviposition rate and emergence (Brunner et al 2001, Schneider et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a few narrow-spectrum (more lepidopteran speciÞc) insecticides have been registered for use on bell pepper, including spinosad (Spintor, Dow AgroSciences LLC, Indianapolis, IN), methoxyfenozide (Intrepid, Dow AgroSciences LLC), and indoxacarb (Avaunt, E. I. DuPont de Nemours and Co., Wilmington, DE). These insecticides provide effective control of most lepidopteran pests, whereas generally having greatly reduced toxicity to natural enemies (Brunner et al 2001;Elzen 2001;Baur et al 2003;Hewa-Kapuge et al 2003;Hill and Foster 2003;Schneider et al 2003;Kring 2003a, 2003b;Carton et al 2003;Haseeb et al 2004Haseeb et al , 2005Villanueva and Walgenbach, 2005).…”
mentioning
confidence: 99%